Diferensiasi Sosial dan Ketahanan Ekonomi Rumah Tangga sebagai Dasar Pembangunan Desa - Sri Anom Amongjati (Asosiasi Ilmuwan Pendidikan, Sosial, dan Humaniora Indonesia, 2026)
Rural communities have heterogeneous structural characteristics because each household has different access to education, employment, land, assets, savings, government assistance, and economic networks. This study aims to explain social differentiation and household economic resilience as a basis for development planning in Pupuan Village, Gianyar, Bali. The study uses a descriptive quantitative approach based on the Precision Village Data Census, with households as the unit of analysis. The data cover 1,411 households in Pupuan Village. The analysis was conducted by constructing a Socioeconomic Structure Index and a Household Economic Resilience Index, followed by cross-tabulation, comparison of index averages, and Spearman correlation analysis. The findings show that households are relatively divided into lower, middle, and upper social strata. Most households are classified as moderately resilient, although they remain weak in terms of economic reserves. The socioeconomic structure has a strong positive relationship with household economic resilience. Access to land, side jobs, government assistance, and livelihood strategies are important indicators in shaping household adaptive capacity. These findings indicate that village development should be directed in a more differentiated manner based on household-level data so that social protection programs, productive asset strengthening, and livelihood diversification can be implemented more accurately and effectively.